First report of 16Sr II‐C subgroup phytoplasma association with Acacia mangium in Tripura, India. Issue 1 (20th December 2019) - Rao, Govind Pratap; Bahadur, Amar; Das, Sukhen Chandra; Ranebennur, Hemavati; Mitra, Surabhi; Kumar, Manish; Kumar, Shailender
Abstract: Leaf yellowing symptoms were observed on Acacia mangium in the Sipahijala district of Tripura, India, during June 2017. Symptomatic and asymptomatic leaf samples (three of each) were collected from roadside trees of A . mangium for DNA extraction using the CTAB method. Amplicons of 1.25 kb and 480 bp were detected in all the symptomatic samples using the phytoplasma‐specific universal 16S rRNA and sec A gene primers. Pair wise sequence analysis of 16S rRNA gene sequences, virtual RFLP and phylogenetic analysis revealed that the phytoplasma strain associated with A . mangium belonged to phytoplasma subgroup 16SrII‐C. This is the first report of an association between the 16SrII‐C subgroup and A . mangium leaf yellowing.